A Detailed Post Mortem Analysis of Solid Oxide Electrolyzer Cells after Long-Term Stack Operation. Issue 5 (6th April 2018) - Frey, Carolin E.; Fang, Qingping; Sebold, Doris; Blum, Ludger; Menzler, Norbert H.
Abstract : A long-term test with a two-layer solid oxide electrolyzer stack was carried out for more than 20 000 hours. The stack was mainly operated in a furnace environment in electrolysis mode, with 50% humidification of H2 at 800°C, a current density of −0.5 Acm −2 and steam conversion rate of 50%. After ∼18 000 hours of operation in electrolysis mode, the voltage and area specific resistance degradation rates were ∼0.6%/kh and 8.2%/kh, respectively. A detailed post mortem analysis of cells including ICP-OES and microstructural analysis was conducted. Two main degradation phenomena were observed in the cells: In the fuel electrode, the depletion and agglomeration of nickel were visible. At the air electrode, demixing of the air electrode and diffusion of strontium took place. This was observed in the formation of strontium zirconate at the interface between the electrolyte and the GDC barrier layer as well as in the formation of strontium oxide and strontium chromate on top of the cells. Strontium oxide was even found in pores on top of the electrolyte.